2016
DOI: 10.1111/joim.12462
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic and nondiabetic patients with nonalcoholic fatty liver disease have an impaired incretin effect and fasting hyperglucagonaemia

Abstract: Patients with NAFLD have a reduced incretin effect and fasting hyperglucagonaemia, with the latter occurring independently of glucose (in)tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 51 publications
3
56
1
1
Order By: Relevance
“…Despite reduced L-cell density, enteroendocrine function seemed to be preserved through higher intracellular GLP-1 content. Recent papers showed that during OGTT in various types of metabolic diseases, GLP-1 release is delayed along with prolongation of the postprandial hyperglycaemia [24], [25], [26]. In our study, GLP-1 secretion was measured belatedly, 30 min after GLP-1 secretagogue administration.…”
Section: Discussionmentioning
confidence: 63%
“…Despite reduced L-cell density, enteroendocrine function seemed to be preserved through higher intracellular GLP-1 content. Recent papers showed that during OGTT in various types of metabolic diseases, GLP-1 release is delayed along with prolongation of the postprandial hyperglycaemia [24], [25], [26]. In our study, GLP-1 secretion was measured belatedly, 30 min after GLP-1 secretagogue administration.…”
Section: Discussionmentioning
confidence: 63%
“…Consistent with this proposed feedback loop, individuals with glucagon-producing tumours have decreased levels of plasma amino acids [11,31], and, conversely, individuals with glucagon receptor mutations [10,32,33] and mice with glucagon receptor deficiency [30,34] exhibit increased levels of plasma amino acids. Hyperglucagonaemia has also been reported in individuals with fatty liver disease independent of their glycaemic status [35], and this has recently been linked to an increased plasma pool of amino acids including alanine, but excluding the BCAAs isoleucine, leucine and valine [36].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of glucagon on NAFLD has not been elucidated. Junker and colleagues [109] have shown that patients with NAFLD have fasting hyperglucagonemia, independent of their glucose tolerance status. According to the authors, this finding suggests that NAFLD might be involved in the generation of hyperglucagonemia in T2D, which is supported by several animal studies [110].…”
Section: Pancreatic Hormones and Nafldmentioning
confidence: 99%